Development and validation of a stability-indicating RP-LC method for the simultaneous determination of otilonium bromide and its expected degradation product in bulk drug and pharmaceutical preparation - El-Kerdawy, Mohamed Mahmoud; El-Bagary, Ramzia Ismail; Elkady, Ehab Farouk; Othman, Ahmed Adel (European Journal of Chemistry, 2016)
A simple, precise, accurate and rapid stability indicating liquid chromatography method had been developed for the simultaneous determination of otilonium bromide (OB) and its expected degradation product; p-aminobenzoic acid (PABA) in bulk powder and pharmaceutical preparation. Chromatographic separation was carried out by isocratic elution on Waters Atlantis C18 column (4.6 × 150 mm, 5 µm) using 2 mM ammonium acetate buffer (pH = 2.35) containing 0.05% TFA: acetonitrile (30:70, v:v) as the mobile phase. The flow rate was 0.8 mL/min with UV detection at 290 nm. Linearity was obtained over a concentration range of 0.5-100 μg/mL with regression coefficient of 1 for OB, and over concentration range of 1-50 μg/mL with regression coefficient of 0.9998 for PABA. The values of LOD and LOQ were found to be 0.0665 and 0.2018 μg/mL for OB and 0.1974 and 0.598 μg/mL for PABA, respectively. The method was validated as per ICH guidelines. The method was successfully applied to the determination of the drug in bulk powder and pharmaceutical preparation.